Return to Sports Following Anterior Cruciate Ligament Reconstruction – Short Term Follow Up (Medical Forum Monthly, 2024)
Objective: To determine the factors which will help in return to the sports the following anterior cruciate ligament reconstruction and compare the study results to the previous international results.Study Design: Prospective descriptive case series study.Place and Duration of Study: This study was carried out at the Department of Orthopedic Surgery, King Abdul Aziz Hospital Jeddah from June 2011 to May 2014.Patients and Methods: 40 patients were included in this study. These patients were admitted in the Department of Orthopedic Surgery one day before and performed arthroscopic assisted ACL reconstruction at King Abdul Aziz Hospital Jeddah with anterior cruciate ligaments tear and ± meniscal injuries. Those patients having associated meniscal injury were included and dealt arthroscopically. The patients were excluded from the study who had associated fracture and also posterior cruciate injuries.Results: The mean age of patients was 22.0±8.0 years. All the patients were male and soccer players. The mode of injury was sports. The hamstring tendons were taken and applied as grafts in all the cases. Rehabilitations protocol was carried out in the postoperative period in routine rehabilitation clinics. The factors responsible for the determination of the return include age of the patients, how complex injuries, the psychological motivation and delay in surgery. The data was collected and analyzed with the self-generated questionnaire performa taking the help of Lyshlohm Knee Scoring System. The psychologically strong patients with will and wish were excellent in return to their sports activity.Conclusion: Rehabilitation compliance for the young psychologically motivated individuals operated early were having best score with excellent return to sports. So these factors should be considered before the consideration of ACL reconstruction.